2015
DOI: 10.1016/j.vaccine.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of early-activated hapten-specific B cell subsets predicts the efficacy of vaccines for nicotine dependence

Abstract: Therapeutic vaccines for nicotine addiction show pre-clinical efficacy. Yet, clinical evaluation of the first-generation nicotine vaccines did not meet expectations because only a subset of immunized subjects achieved effective serum antibody levels. Recent studies suggest that vaccine design affects B cell activation, and that the frequency of the hapten-specific B cell subsets contributes to vaccine efficacy against drugs of abuse. To extend this hypothesis to nicotine immunogens, we synthesized a novel hapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…33,34 The strength of this approach is that very rare antigen-specific B and T cells are detected prior to, or shortly after immunization. [35][36][37][38][39] To date, this approach has been used to test the effect of hapten structure, 40,41 adjuvant, 42 or host genetics 42 on the B cell response to vaccines for SUD. This strategy has also been used to study the relationship between antigen-specific B and T cells and individual variability in post-immunization Ab titers, or efficacy against drug distribution and drug-induced behavior in mice.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…33,34 The strength of this approach is that very rare antigen-specific B and T cells are detected prior to, or shortly after immunization. [35][36][37][38][39] To date, this approach has been used to test the effect of hapten structure, 40,41 adjuvant, 42 or host genetics 42 on the B cell response to vaccines for SUD. This strategy has also been used to study the relationship between antigen-specific B and T cells and individual variability in post-immunization Ab titers, or efficacy against drug distribution and drug-induced behavior in mice.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%
“…This strategy has also been used to study the relationship between antigen-specific B and T cells and individual variability in post-immunization Ab titers, or efficacy against drug distribution and drug-induced behavior in mice. 41,43 These studies found that na€ ıve and early-activated B cells can discriminate between structurally-related haptens, and that the size of the polyclonal hapten-specific B cell population determines vaccine immunogenicity and efficacy against drugs of abuse. 40,41 When comparing individuals, differences in the population size of hapten-specific B cells and carrier-specific T cells are found before and/or after immunization in individual mice, and correlate to vaccine immunogenicity and efficacy.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%
See 3 more Smart Citations